Affective motivations for borrowing: Performing local identity through loan phonology. (July 2016) - Babel, Anna M.
Abstract: Speakers of a contact variety of Bolivian Spanish use aspirates and ejectives, primarily on Quechua loanwords, due to long-term, intense societal contact with Quechua. Speakers employ aspirates and ejectives to express affective stances such as anger, humor, and intimacy, and to index a local identity. Affective ties to language through expressive and sound symbolic associations motivate the use of aspirates and ejectives in the sound system of this language. The question of what linguistic features mean to people is key to understanding how they are transferred between languages and why they are maintained by members of a speech community. Highlights: Speakers of Bolivian Spanish use aspirates and ejectives on Quechua loanwords. The use of aspirates and ejectives indexes affective stances and a rural identity. Social motivations are key to the maintenance of non-canonical Spanish sounds. Language shift produces a different outcome than borrowing from a foreign language.